Challenges of the present and future perspectives of the English language - ULAYWI, RAGHAD KHALAF (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT Globally, the ascendancy of the English language leads to the violent commotion, which is minatory in the present and near future. In addition, the English language needs to be survived and flourished by professional people (teachers). The qualifications of an English language teacher are essential in this aspect. The numbers of good qualifications for the teacher are as follows; he should be secured, stimulated, and independent. The innovative teacher has a lot of information and feels highly confident with his students. Therefore English is a unique and yarn language that needs the essential qualities to continue surviving in the present and forecast the future. RESUMEN A nivel mundial, el predominio del idioma inglés conduce a una conmoción violenta que es insignificante en el presente y el futuro cercano. Además, el idioma inglés debe ser sobrevivido y prosperado por personas profesionales (profesores). Las calificaciones de profesor de lengua inglesa son fundamentales en este aspecto. Los números de buenas calificaciones para maestro son los siguientes: debe ser asegurado, estimulado e independiente. El maestro innovador tiene mucha información y se siente muy seguro con sus alumnos. Por lo tanto, el inglés es el idioma único e intrincado que necesita las cualidades esenciales para continuar sobreviviendo en el presente y el futuro.